Risk Management Analysis and Profit Maximization of Indonesian Millennials Investing in Cryptocurrencies - Munadiati Munadiati; Anis Kurlillah; Iskandar Iskandar; Abdul Hamid (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2022)
Cryptocurrency investment has become a phenomenon in various countries, including Indonesia, especially among millennials. In February 2021, there were 4.2 million cryptocurrency investors in Indonesia, most of them are millennials. A cryptocurrency is a new form of investment, which has high volatility, where investors are faced with the risk of very volatile price changes. This study aims to determine the millennial generation's understanding of the risks of investing in cryptocurrency and how the millennial generation manages risk and maximizes profits when investing in cryptocurrency assets. The methodology used in this study is a qualitative method by conducting in-depth interviews, where the respondents are cryptocurrency investors with an age range of birth from 1980 to 2003. The results of this study indicate that the millennial generation has realized the risks faced when investing in cryptocurrencies and the risk management and profit maximization used are by determining stop loss and take profit points, waiting and selling, applying the dollar-cost averaging method, and investing long-term. By using this method, investors in this study avoid risk and get maximum profit when investing in cryptocurrency. Keywords: Risk Management, Profit maximization, Investment, Cryptocurrency, Millenial